Starting to gather smog data? - Erwin Wasey, Ruthrauff; Beckman Instruments, Inc. (1964)
This advertisement for Beckman Instruments targets people who are monitoring their companies' emissions, encouraging them to get a better understanding of their "problems." It positions air pollution as something to be dealt with by a company or individual, and as a problem that can be solved with enough, or the right kind of, quantitative data. Beckman Instruments, Inc. became interested in measuring, controlling, and fighting air pollution in the late 1940s and early 1950s, when company president Arnold O. Beckman became the scientific adviser to the Los Angeles Chamber of Commerce’s Air Pollution Control Officer. Many of the instruments that were developed by Beckman Instruments in the 1940s and 1950s as standalone items became incorporated into or re-purposed as smog-fighting systems.
Keywords: Air quality management; Smog; Air--Pollution; Beckman Instruments, Inc.; Air--Pollution--Measurement